(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In a library, circulation and shelving of reading materials is a time-consuming task that consumes the majority of the library staff’s time. Because RFID minimises the time it takes to undertake circulation tasks, it is a viable solution to this problem. The benefits and limitations of RFID usage in libraries are discussed in this article, as well as the components and technological aspects of a modern RFID library system. It also looks at the existing level of RFID deployment in Indian libraries and makes some suggestions. Applications that use radio frequency identification (RFID) to provide massive access, huge data storage, as well as reprogramming. RFID technology may improve operational efficiency and accuracy. One of the most important variables determining whether RFID will be adopted in libraries is the cost. Despite the fact that RFID has increased library efficiency, the core of the library service has not altered.